Retraction: Ni2[Lncl6] (Ln = Euii, Ceii, Gdii): The First Lnii Compounds Stabilized in a Pure Inorganic Lattice (Chemical Communications 2018 54 (7531-7534) Doi: 10.1039/C7cc09921e) - Venegas-Yazigi, D; Venegas-Yazigi, D (Royal Society of Chemistry, 2019)
We, the named authors hereby wholly retract this Chemical Communications article due to concerns with the interpretation of the data in the published article. In the article crystal structures were identified by the authors as Ni2[LnCl6]. Subsequent analysis of the data by independent experts suggest that the structure is a better match for the compound [Ni(NH3)6]Cl2. The authors suggest that there may be a mixture of compounds present in their material, but it has not been possible to obtain convincing data for the lanthanide crystals at this time. Given the significance of the concerns, the validity of the data and, therefore, the conclusions presented in this paper are no longer reliable. Signed: Bianca Baldo, Francisco Rubio, Andres Vega, Nathalie Audebrand, Diego Venegas-Yazigi and Vero nica Paredes-Garc a Date: 7th October 2019 Erwin Flores was contacted but did not respond. Retraction endorsed by Richard Kelly, Executive Editor, Chemical Communications. © 2019 The Royal Society of Chemistry.